Changing epidemiology and functional outcomes of inpatient rehabilitation in Asian traumatic brain injury cases before and during the COVID-19 pandemic: a retrospective cohort study - Chua, Karen Sui Geok (2023)
Background: This study aimed to compare acute injury and rehabilitation characteristics for traumatic brain injury (TBI) inpatients during the pre and post COVID-19 pandemic periods. Methods: A retrospective study of TBI inpatients between 1 April 2018 and 31 December 2019 (pre COVID-19 period), and 1 July 2020 and 31 March 2022 (post COVID-19 period) was performed to compare demographics, premorbid comorbidity, TBI characteristics, rehabilitation complications, admission and discharge functional independence measure (FIM®), length of stay and discharge status. Results: A total of 187 data sets were analyzed (82 pre COVID-19 and 105 post COVID-19). Post COVID-19 TBI inpatients were older by 11 years (pre COVID-19 mean 55 years vs. post COVID-19 mean 66 years, and p < 0.001), with 23% higher female inpatients (pre COVID-19 13.4% vs. post COVID-19 36.2%, and p < 0.001) and 25% higher presence of comorbidities (pre COVID-19 52.4% vs. post COVID-19 77.1%, and p < 0.001). In the post COVID-19 group, total discharge FIM (Td-FIM) was significantly lower by ~12 points (pre COVID-19 94.5 vs. post COVID-19 82, and p = 0.011), Td-FIM ≥ 91 was lower by ~18% (pre COVID-19 53.7% vs. post COVID-19 36.2%, and p = 0.017), and the need for caregivers increased by ~17% (pre COVID-19 68% vs. post COVID-19 85.4%, and p = 0.006) Conclusions: Our findings signal a demographic shift towards older, frailer TBI with lower functional independence levels post COVID-19.